CardioMems® device implantation reduces repeat hospitalizations in heart failure patients: A single center experience. (February 2019) - Assaad, Mahmoud; Sarsam, Sinan; Naqvi, Amir; Zughaib, Marcel
Introduction: Hospital readmission for congestive heart failure remains one of the most important economic burdens on healthcare cost. The implantation of a wireless pressure monitoring device (CardioMEMS®) had led to nearly 40% reduction in readmission rates in the landmark CHAMPION trial. We aim to study the effectiveness of this wireless device in reducing heart failure admissions in a real-world setting. Methods: This is a retrospective chart review of patients with recurrent admissions for heart failure implanted with the wireless pressure monitoring system (CardioMEMS®) at our institution. We studied the total number of all-cause hospital admissions as well as heart failure-related admissions pre- and post-implantation. Results: A total of 27 patients were followed for 6–18 months. The total number of all-cause hospital admissions prior to device implantation was 61 admissions for all study patients, while the total number for the post-implantation period was 19, correlating with 2.26 + 1.06 admissions/person-year prior to device implantation versus 0.70 + 0.95 admissions/person-year post-implantation (p-value < 0.001). For heart failure-related admissions, the total number prior to device implantation was 46 compared to 9 admissions post device implantations, correlating with 1.70 + 1.07 admissions/person-years pre-implantation versus 0.33 + 0.62 admissions/person-years post-implantation (p-value < 0.001). This translates to 80.4% and 68.9% reduction in heart failure and all-cause admissions, respectively. Conclusion: In a real-world setting, the implantation of a wireless heart failure monitoring system in patients with heart failure and class III symptoms has resulted in 80.4% reduction in heart failure admissions and 69% reduction in all-cause admissions.